2017
DOI: 10.1155/2017/6091923
|View full text |Cite
|
Sign up to set email alerts
|

Spatholobus suberectus Exhibits Antidiabetic Activity In Vitro and In Vivo through Activation of AKT‐AMPK Pathway

Abstract: Glucose deposition in peripheral tissue is an important parameter for the treatment of type 2 diabetes mellitus. The aim of this study was to investigate the effects of Spatholobus suberectus (Ss) on glucose disposal in skeletal muscle cells and additionally explore its in vivo antidiabetic potential. Treatment of ethanolic extract of S. suberectus (EeSs) significantly enhanced the glucose uptake, mediated through the enhanced expression of GLUT4 in skeletal muscle via the stimulation of AKT and AMPK pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 43 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…However, other scientists found that in the L6 muscle cell line, this mechanism is not involved, suggesting the mechanism is still unclear. In the antioxidant assays, significant scavenging activity of free Furthermore, Ss showed potent antioxidant ability that helped in counteracting the effects of diabetes and also blocked gluconeogenesis in diabetic mice (Zhao et al, 2017).…”
Section: Hypothalamusmentioning
confidence: 99%
“…However, other scientists found that in the L6 muscle cell line, this mechanism is not involved, suggesting the mechanism is still unclear. In the antioxidant assays, significant scavenging activity of free Furthermore, Ss showed potent antioxidant ability that helped in counteracting the effects of diabetes and also blocked gluconeogenesis in diabetic mice (Zhao et al, 2017).…”
Section: Hypothalamusmentioning
confidence: 99%
“…The antidiabetic effect of S . suberectus in type 1 diabetes is already known [ 18 ] but the effect of S . suberectus on AGEs-induced diabetic nephropathy and the underlying mechanism are yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we evaluated the other diabetes-inducing factors such as dyslipidemia, urine ACR, and glycotoxicity in this study. Zhao et al [ 18 ] used 100% ethanol extract of S . suberectus and C57BL/6j mice, whereas our experiment used 70% ethanol extract and db/db mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations